Daily rhythms of catalase and glutathione peroxidase expression and activity are endogenously driven in the hippocampus and are modified by a vitamin A-free diet - Navigatore Fonzo, Lorena Silvina (2013)
Objectives: Alterations in enzymatic antioxidant defense systems lead to a deficit of cognitive functions and altered hippocampal synaptic plasticity. The objectives of this study were to investigate endogenous rhythms of catalase (CAT) and glutathione peroxidase (GPx) expression and activity, as well as CREB1 mRNA, in the rat hippocampus, and to evaluate to which extent the vitamin A deficiency could affect those temporal patterns. Methods: Rats from control and vitamin A-deficient (VAD) groups received a diet containing 4000 IU of vitamin A/kg diet, or the same diet devoid of vitamin A, respectively, during 3 months. Rats were maintained under 12-hour-dark conditions, during 10 days before the sacrifice. Circadian rhythms of CAT, GPx, RXRγ, and CREB1 mRNA levels were determined by reverse transcriptrase polymerase chain reaction in hippocampus samples isolated every 4 hours during a 24-hour period. CAT and GPx enzymatic activities were also determined by kinetic assays. Regulatory regions of clock and antioxidant enzymes genes were scanned for E-box, RXRE, and CRE sites. Results: E-box, RXRE, and CRE sites were found on regulatory regions of GPx and CAT genes, which display a circadian expression in the rat hippocampus. VAD phase shifted CAT, GPx, and RXRγ endogenous rhythms without affecting circadian expression of CREB1. Discussion: CAT and GPx expression and enzymatic activity are circadian in the rat hippocampus. The VAD affected the temporal patterns antioxidant genes expression, probably by altering circadian rhythms of its RXR receptors and clock factors; thus, it would impair the temporal orchestration of hippocampal daily cognitive performance.